C–H functionalization reactions enabled by hydrogen atom transfer to carbon-centered radicals - Sarkar, Sumon (Chem Sci, 2020)
Selective functionalization of ubiquitous unactivated C–H bonds is a continuous quest for synthetic organic chemists. In addition to transition metal catalysis, which typically operates under a two-electron manifold, a recent renaissance in the radical approach relying on the hydrogen atom transfer (HAT) process has led to tremendous growth in the area. Despite several challenges, protocols proceeding via HAT are highly sought after as they allow for relatively easy activation of inert C–H bonds under mild conditions leading to a broader scope and higher functional group tolerance and sometimes complementary reactivity over methods relying on traditional transition metal catalysis. A number of methods operating via heteroatom-based HAT have been extensively reported over the past few years, while methods employing more challenging carbon analogues have been less explored. Recent developments of mild methodologies for generation of various carbon-centered radical species enabled their utilization in the HAT process, which, in turn, led to the development of remote C(sp(3))–H functionalization reactions of alcohols, amines, amides and related compounds. This review covers mostly recent advances in C–H functionalization reactions involving the HAT step to carbon-centered radicals.